Current challenges in the respiratory management of preterm infants at a regional and national level - Algarni, Saleh (2020)
Preterm birth remains a leading public health challenge and is associated with significant mortality and long-term morbidity. Bronchopulmonary dysplasia (BPD) is one of the most common complications of prematurity and is associated with life-long poor neurodevelopmental and respiratory outcomes. The aims of this thesis were to understand the challenges facing the respiratory management of high-risk preterm infants and explore approaches to overcome these that could potentially improve outcomes.